The meaning of proofs: mathematics as storytelling - Lolli, Gabriele 1942- (The MIT Press, 2022)
"This book introduces readers to the narrative structure of mathematical proofs and why mathematicians communicate that way, drawing examples from classic literature and employing metaphors and imagery"